Effects of binder choice in converter and blast furnace sludge briquette preparation: Environmental and practical implications - Drobíková, Klára; Vallová, Silvie; Motyka, Oldřich; Mamulová Kutláková, Kateřina; Plachá, Daniela; Seidlerová, Jana (Waste management (New York, N.Y.), 2018)
Blast furnace and converter sludges are fine-grained waste materials characterized as dangerous waste with a negative impact on the environment. One way of recycling of such materials is briquetting followed by reuse of the material in the blast furnace. In the briquetting process, an important step is the choice of the binder suitable for manufacturing the briquettes with suitable mechanical properties. In this work, the effect of the binder choice (laundry starch UNIPRET, Portland cement) on the reduction of iron oxides in the assessed waste materials during thermal treatment (900, 1000, 1100 °C) is evaluated. Simultaneously, the effect of the binder choice on the amount and composition of the resulting waste gas was evaluated as well as its possible impact on the environment. The performed experiments proved the mutual relationship between the level of iron oxides to metal iron conversion, the binder content and retention temperature. Type of binder also affected the volume of the resulting waste gas. Factor analysis for mixed data (FAMD) proved that the resulting concentrations of the assessed hydrocarbons were correlated (apart from ethyne) and that they are closely associated with the binder applied. Conversely, the concentrations of ethyne, carbon monoxide and carbon dioxide were not associated with the binder but with the retention temperature. FAMD did not show any direct effect of final retention temperature on the amount of the rest of the resulting hydrocarbons. In comparison with the starch-containing briquettes, the cement-containing briquettes were also proved to lead to lower resulting concentrations of PAHs in the waste gas.
Keywords: Metals; Construction Materials; konstrukční materiály; Sewage; Recycling; Briquetting; Thermal treatment; kovy; Converter sludge; Binder; Temperature; Blast furnace sludge; recyklace; odpadní vody; Waste gas; teplota